Performance analysis of OSPF and EIGRP protocols in a very dynamic network - Ahmed Mohammed, Abdul Nasser; Khatun, Sabira (2009)
Fast failure critical to traffic protection where restoration in high-speed network is always needed when failure occurs. These networks use routing protocols in communication with each other. Routing protocols are classified under two major types link state protocol and distance vector protocol. In this article a comparison between Open Short Path First (OSPF), which is a link state protocol and Enhanced Interior Gateway Protocol (EIGRP) which is a distance vector protocol. This study intends to show which one of these two protocols could be used in a very dynamic environment like airspace networks, which links failure is one of its features. A simulation was done by using OPNET 'IT GURU' to identify which protocol is more efficient and reliable. In this study a fast normal loaded IP network carrying FTP traffic between end points nodes is simulated. A network which has three airborne levels is configured. The results show that all IP traffics are dropped when the OSPF protocol is implemented whereas all IP traffics were sent to the destination when EIGRP is implemented due to the fast traffic rerouting. Furthermore, this study also proves that OSPF does not meet the performance requirements of the airspace network. This is due to its inefficient rerouting when a link failure happens. Finally it shows that EIGRP has higher efficiency and reliability in dynamic networks environment.